HERMENEUTIKA, MAKNA DAN KOMUNIKASI DALAM PERSPEKTIF HANS-GEORG GADAMER - Constantin, Natasha Astrid; Sitorus, Fitzerald Kennedy (Fakultas Ilmu Sosial UIN Sumatera Utara Medan, 2024)
This study investigates the notion of comprehension and significance in communication via the perspective of Hans-Georg Gadamer. The subject matter revolves on hermeneutics, which pertains to the aptitude for precisely understanding the message sent by an individual via language. Gadamer defines hermeneutics as a process of interpretive understanding used to extract an interpretation of the transmitted information. This study highlights the importance of understanding in hermeneutics for interpreting the present situation. This study delves further into the influence of Gadamer's viewpoint on the notion of significance and understanding in the field of communication.